Knowledge Management System Sharing Record Teknisi Berbasis Android Pada PT. CNC Part Teknika - A. Yudi Permana; Ananto Tri Sasongko; Rita Purnamasari (Teknik Informatika, Universitas Pelita Bangsa, 2022)
Abstract Reports contain facts about news, information, notifications, and forms of activities relating to accountability. Job reports that have not been properly documented are also an obstacle for the company when a technician resigns, making it difficult to distribute the knowledge possessed by the old technician to the new technician. Knowledge Management System is one way to identify, select, disseminate and disseminate important information and expertise in an organization as an effort to develop productivity and work performance so as to increase the competitiveness of the organization. The development of information systems is fast, accurate and up to date available in the plat form, such as Android. In this case, PT. CNC Part Teknika which is engaged in the field of General Trading and Service, still uses a manual system for making information job report. One example of the report method they used paper for media report. However, this reporting method is easily lost and damaged. This research aimed to design application knowledge management system job report based on android system. In designing this application using the XP (Extreme programing) and UML (Unified Modeling Language) methods. This is expected to documenting the knowledge of technicians in handling service and help facilitate the process of making reports is up to date for technician at PT. CNC Part Teknika. This application is useful for technician workers of PT. CNC Part Teknika using a database that can be used easily and quickly. Keywords: Reports, Knowledge Management System, android, General Trading and Service, UML.